The Effect of Giving Liquid Organic Fertilizer to Sawia Putih Waste (Brassica pekinensis L.) on Plant Growth Tomato (Lycopersicum esculentum Mill.). - Mauliani Mauliani; Hafnati Rahmatan; Wardiah Wardiah; Muhibbuddin Muhibbuddin; Nazar Muhammad (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Tomatoes are one of the most common fruits and vegetables in Indonesia. The use of fertilizers in the right amount, especially organic fertilizers as a substitute for chemical fertilizers, is. one way to increase the growth and production of tomatoes. Chicory waste (Brassica pekinensis L.) is vegetable waste that can be used as organic fertilizer because it contains organic compounds which are good for liquid organic fertilizer. This study aims to determine the effect of liquid organic fertilizer from chicory waste on the growth of tomato plants. The approach used in this study was quantitative, the type of research used was experimental using a completely randomized design (CRD) with 4 treatments, namely P0 (control), P1 (20 %), P2 (40 %), and P3 (60 %) ). Data.were.analyzed.using.Analysis of Variance (ANOVA) and Least Significant Difference (LSD) at a significant level of 0.05. The results showed that there was a significant effect on the growth of tomatoes on the parameters of plant height and number of leaves. The conclusion of this study is that the application of liquid organic fertilizer from chicory waste has a significant effect on the growth of tomato plants.Keywords: chicory waste, tomatoes, growthTomat adalah tanaman hortikultura yang merupakan jenis buah dan sayuran yang paling umum di Indonesia. Penggunaan pupuk dalam jumlah yang tepat, khususnya pupuk organik sebagai pengganti pupuk kimia, merupakan salah satu cara untuk meningkatkan pertumbuhan dan produksi tomat.Limbah sawi putih (Brassica pekinensis L.) merupkan limbah sayuran yang dapat dijadikan sebagai pupuk organik karena memiliki kandungan senyawa organik yang baik untuk dijadikan pupuk organik cair. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian pupuk organik cair limbah sawi putih terhadap pertumbuhan tanaman tomat. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif, jenis penelitian yang digunakan adalah eksperimental dengan menggunakan Rancangan Acak Lengkap (RAL) dengan 4 perlakuan, yaitu P0 (kontrol), P1 (20%), P2 (40%), dan P3 (60%). Data dianalisis menggunakan Analisis Varian dan Uji Lanjut Beda Nyata Terkecil (BNT) pada taraf signifikan 0,05. Hasil penelitian menunjukkan bahwa terdapat pengaruh nyata terhadap pertumbuhan tomat pada parameter tinggi tanaman, dan jumlah daun. Kesimpulan penelitian ini adalah pemberian pupukkkorganik cair limbah sawi putih berpengaruh nyata terhadap pertumbuhn tanaman tomat.Kata kunci: limbah sawi putih, tomat, pertumbuhan